The efficacy and safety of eravacycline compared with current clinically common antibiotics in the treatment of adults with complicated intra-abdominal infections: A Bayesian network meta-analysis - Meng, Rui; Guan, Xin; Sun, Lei; Fei, Zhengyang; Li, Yuxin; Luo, Mengjie; Ma, Aixia; Li, Hongchao (Frontiers in Medicine, 2022)
Background Eravacycline is a novel, fully synthetic fluorocycline antibiotic for the treatment of adults with complicated intra-abdominal infections (cIAIs). However, the efficacy and safety of eravacycline compared with current clinically common antibiotics remain unknown. Objective This study aims to compare the efficacy and safety of eravacycline and other clinically common antibiotics in China, including tigecycline, meropenem, ertapenem, ceftazidime/avibactam+metronidazole, piperacillin/tazobactam, imipenem/cilastatin, and ceftriaxone+metronidazole, for the treatment of adults with cIAIs and to provide a reference for clinical choice. Methods The PubMed, Embase, Cochrane Library, and ClinicalTrials.gov databases were electronically searched to collect clinical randomized controlled studies (RCTs) comparing different antibiotics in the treatment of patients with cIAIs from inception to June 1, 2021. Two reviewers independently screened the literature, extracted data, and evaluated the risk of bias in the included studies. Results A total of 4050 articles were initially retrieved, and 25 RCTs were included after screening, involving 8 treatment therapies and 9372 patients. The results of network meta-analysis showed that in the intention-to-treat (ITT) population, the clinically evaluable (CE) population, and the microbiologically evaluable (ME) population, the clinical response rate of eravacycline was not significantly different from that of the other 7 therapies (P>0.05). In terms of microbiological response rate, eravacycline was significantly better than tigecycline [tigecycline vs. eravacycline: RR=0.82, 95%CI (0.65,0.99)], and there was no significant difference between the other 6 regimens and eravacycline (P>0.05). In terms of safety, the incidence of serious adverse events, discontinuation rate, and all-cause mortality of eravacycline were not significantly different from those of the other 7 treatment therapies (P>0.05). Conclusion Based on the evidence generated by the current noninferiority clinical trial design, the efficacy and safety of eravacycline for the treatment of adults with cIAIs are not significantly different from those of the other 7 commonly used clinical antibiotics in China. In terms of microbiological response rate, eravacycline was significantly better than tigecycline. In view of the severe multidrug-resistant situation in China, existing drugs have difficulty meeting the needs of clinical treatment, and the new antibacterial drug eravacycline may be one of the preferred options for the treatment of cIAIs in adults.